2022
DOI: 10.3389/fmolb.2022.957502
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles and Risks of G-Quadruplex Regulation: Recognition Targets of ALS-Linked TDP-43 and FUS

Abstract: A non-canonical DNA/RNA structure, G-quadruplex (G4), is a unique structure formed by two or more guanine quartets, which associate through Hoogsteen hydrogen bonding leading to form a square planar arrangement. A set of RNA-binding proteins specifically recognize G4 structures and play certain unique physiological roles. These G4-binding proteins form ribonucleoprotein (RNP) through a physicochemical phenomenon called liquid-liquid phase separation (LLPS). G4-containing RNP granules are identified in both pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 114 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…1 D). The binding of G4-RNA to specific interacting proteins with multiple binding modules often does not migrate normally when using a non-denaturing acrylamide gel 6 . As a result, this attempt was effective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 D). The binding of G4-RNA to specific interacting proteins with multiple binding modules often does not migrate normally when using a non-denaturing acrylamide gel 6 . As a result, this attempt was effective.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, identifying and analyzing the state of RNA molecules common to all is essential. Indeed, without exception, all these RNAs and RBPs are associated with G-quadruplexes (G4) and are components of ribonucleoprotein (RNP) granules assembled through liquid–liquid phase separation (LLPS) 6 (Table S1 ). This is surprising because there are not many RBPs that specifically recognize G4 7 , 8 .…”
mentioning
confidence: 99%
“…G4 ligands have been shown to ameliorate the presence of ALS aggregates in cells 26,52 . The ligands have been speculated to act by disrupting the toxic downstream functions of C9orf72 - thought to underpin aggregation 52 .…”
Section: Resultsmentioning
confidence: 99%
“…G4 ligands have been shown to ameliorate the presence of ALS aggregates in cells 26,52 . The ligands have been speculated to act by disrupting the toxic downstream functions of C9orf72 - thought to underpin aggregation 52 . Having demonstrated that mG4s alone are able to prompt aggregation in protein-free samples, we asked whether G4 ligands could destabilise the condensates by promoting the formation of unimolecular as opposed to multimolecular G-quadruplexes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the FUS is an important model for investigating the LLPS behavior of IDPs/IDRs, and there are abundant studies for LLPS using the FUS model. Some functional MLOs containing FUS are modulated by the recognition of FUS to special RNA fragments [ 6 , 16 , 26 ]. Kang et al found that the LLPS of FUS whose aggregation leads to ALS/FTD is enhanced at low concentrations for ATP but is dissolved at high concentrations [ 27 ].…”
Section: Introductionmentioning
confidence: 99%